Treatments for improving tree growth, yield and fruit quality and for reducing double fruit and deep suture incidence in “Desert red” peach trees - Zayan, M. A.; Mikhael, G. B.; Okba, S. K. (International Journal of Horticultural Science, 2016)
Five years old “Desert red” peach trees budded on Nemaguard rootstock and grown in sandy soil at commercial orchard Al-Nubaria city, El-Behira Governorate-Egypt were treated with some agricultural treatments involving thinning out pruning, fruit thinning and foliar application of potassium silicate (25% S +10% K2O) at 0.1% and super grow (20% N, 20% P2O5 and 20% K2O) at 0.3% in 2014 and 2015 seasons, to study their effects on yield and fruit quality and the relationship between nutrient balance and yield of “Desert red” peach trees. Beside, testing the influence of used treatments on two physiological disorder, double fruit and deep suture %. Also, economic evaluation of different treatments was done. All obtained data were statistically analyzed using a randomized complete block design. Depending on the obtained results in this study, it could be concluded that application of thinning out pruning 35%, fruit thinning by leaving 15 cm between fruits on one-year old shoot at 20 days after full bloom and foliar application of potassium silicate which sprayed five times during each growing season at fruit set, the second fruit development stage, the beginning of the fruit color change and twice after month from harvest, most profitable treatment for peach trees grown under conditions of this investigation. This treatment gave the best vegetative growth, yield, fruit quality, higher crop value with high net income /fed. from “Desert red” peach trees, in addition, reduced the percentage of double fruit and deep suture by more than 50% in both seasons, therefore, the study recommends this treatment for “Desert red” peach growers.